A DFT investigation on bi-functional {1 2 1} faceted orthorhombic β−Sb2O3 for water splitting application - Harshada A. Barve; Rupali R. Deshmukh; Zeenat A. Shaikh; Balaji G. Ghule; Shoyebmohamad F. Shaikh; Ji-Hyun Jang; Rajaram S. Mane; Krishna Chaitanya Gunturu (Next Materials, 2025)
An investigation into the bi-functional nature of the {1 2 1} plane of β-Sb2O3 during water splitting reactions is conducted using density functional theory calculations, examining oxygen evolution reaction (OER) and hydrogen evolution reaction (HER). The facet's asymmetric geometry and distorted electronic density create active sites that facilitate efficient adsorption of H2O and reaction intermediates during catalytic reaction kinetics. The band structure and density of states (DOS) analysis using the HSE06 functional confirms the presence of lone pairs at metal ions near the valence band maximum, inducing an asymmetric charge distribution across the surface. The OER and HER mechanisms on {1 2 1} faceted orthorhombic β−Sb2O3 are further elucidated using binding energies, adsorption energies, and overpotential details at GGA-PBE as well as GGA-PBE-D3 level of theory. The identification of distinct active sites for OER and HER, further the moderate and excellent calculated lower overpotentials of 1.08 V and 0.11 V for OER and HER processes respectively, underscores the potential of {1 2 1} faceted orthorhombic β-Sb2O3 as a bifunctional electrocatalyst in the technology used for overall water splitting.